2015
DOI: 10.1007/s12230-015-9478-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Farmer Priorities in Potato Production Through Participatory Variety Selection

Abstract: A substantial number of farmers in northwest Ethiopia grow potato in the dry season (BBelmehr^, March to August) when rainfall is not dependable for the growth of the crop, resulting in lower yield. Ethiopian Agricultural Research Institutes have tried to change the situation by releasing new late blight tolerant varieties that potentially could allow for production of the crop in the rainy season (BMeher^, May to October). Despite these efforts, the majority of the farmers still grow potato in the Belmehr sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 14 publications
2
36
0
Order By: Relevance
“…In addition, our agronomic data showed that a twelfth trait, early maturity, is an important trait for meher season production. (Kolech et al 2015b). Six traits (drought tolerance, late blight resistance, high yield, long shelf life, suitability for boiling, and suitability for stew) were considered "very important" by most farmers in both agroecologies.…”
Section: Relative Importance Of the Farmers' Variety Selection Traitsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, our agronomic data showed that a twelfth trait, early maturity, is an important trait for meher season production. (Kolech et al 2015b). Six traits (drought tolerance, late blight resistance, high yield, long shelf life, suitability for boiling, and suitability for stew) were considered "very important" by most farmers in both agroecologies.…”
Section: Relative Importance Of the Farmers' Variety Selection Traitsmentioning
confidence: 99%
“…Tuber size is related to high yield and good marketability. Although early maturity (and correlated early flowering) are important traits for breeders seeking to develop new varieties for Meher season production, close to 40% of the farmers did not consider the traits "very important" because they can adjust the varieties they grow each year depending on when the rain starts (Kolech et al 2015b). When there is early rainfall in the growing season, they plant late maturing varieties and vice versa.…”
Section: Relative Importance Of the Farmers' Variety Selection Traitsmentioning
confidence: 99%
See 3 more Smart Citations